Cloning, expression in Escherichia coli, and characterization of cellulolytic enzymes of Azoarcus sp., a root-invading diazotroph. - Reinhold-Hurek, B (1993)
We screened members of a new genus of grass-associated diazotrophs (Azoarcus spp.) for the presence of cellulolytic enzymes. Out of five Azoarcus strains representing different species, only in the endorhizosphere isolate BH72, which is also capable of invading grass roots, was significant endoglucanase activity, in addition to beta-glucosidase and cellobiohydrolase activity, present. Reducing sugars were readily released from medium-viscosity carboxymethylcellulose (CMC), but neither CMC, cellulose filter strips, Avicel, cellobiose, nor D-glucose served as the sole carbon source for growth of Azoarcus spp. Clones from a plasmid library of strain BH72 expressed all three enzymes in Escherichia coli, apparently not from their own promoter. According to restriction endonuclease mapping and subclone analysis, beta-glucosidase and cellobiohydrolase activities were localized on a single 2.6-kb fragment not physically linked to a 1.45-kb fragment from which endoglucanase (egl) was expressed. Two isoenzymes of endoglucanase probably resulting from proteolytic cleavage had pI values of 6.4 and 6.1 and an apparent molecular mass of approximately 36 kDa. Cellobiohydrolase and beta-glucosidase activity were conferred by one enzyme 41 kDa in size with a pI of 5.4, which we classified as an unspecific exoglycanase (exg) according to substrate utilization and specificity mapping; hydrolysis of various oligomeric substrates differentiated it from endoglucanase, which degraded substituted soluble cellulose derivatives but not microcrystalline cellulose. Both enzymes were not excreted but were associated with the surface of Azoarcus cells. Both activities were only slightly influenced by the presence of CMC or D-glucose in the growth medium but were enhanced by ethanol. egl was located on a large transcript approximately 15 kb in size, which was detectable only in cells grown under microaerobic conditions on N2. Surface-bound exo- and endoglucanases with some unusual regulatory features, detected in this study in a strain which is unable to metabolize cellulose or sugars, might assist Azoarcus sp. strain BH72 in infection of grass roots.